2011
DOI: 10.1088/0004-637x/729/2/97
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Dispersal of an Active Region: Quantifying Energy Input Into the Corona

Abstract: In this paper a new technique for modeling non-linear force-free fields directly from line of sight magnetogram observations is presented. The technique uses sequences of magnetograms directly as lower boundary conditions to drive the evolution of coronal magnetic fields between successive force-free equilibria over long periods of time. It is illustrated by applying it to MDI observations of a decaying active region, NOAA AR 8005. The active region is modeled during a 4 day period around its central meridian … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 48 publications
5
136
0
Order By: Relevance
“…Here we discuss observational results relevant to the decay of ARs. Mackay et al (2011) carried out careful magnetic field measurements over four days spanning the CMP of the AR, tracking short-term evolution of magnetic flux, flux imbalance and separation between the centre of gravity of positive and negative polarities. The latter was determined by a vector S( ) as…”
Section: Fragmentation Of Sunspots and The Re-establishment Of Convecmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we discuss observational results relevant to the decay of ARs. Mackay et al (2011) carried out careful magnetic field measurements over four days spanning the CMP of the AR, tracking short-term evolution of magnetic flux, flux imbalance and separation between the centre of gravity of positive and negative polarities. The latter was determined by a vector S( ) as…”
Section: Fragmentation Of Sunspots and The Re-establishment Of Convecmentioning
confidence: 99%
“…Using the magnetic observational data (61 MDI magnetograms) as lower boundary conditions, Mackay et al (2011) carried out a time-dependent non-linear force-free field (NLFFF) quasi-static modelling in order to study the build-up of free magnetic energy and coronal magnetic helicity resulting from the dispersal of the decaying AR 8005. The novelty of their modelling is that it is data-driven: the successive magnetograms drive the evolution of the coronal magnetic fields between successive force-free equilibria.…”
Section: Fragmentation Of Sunspots and The Re-establishment Of Convecmentioning
confidence: 99%
See 1 more Smart Citation
“…For the three-dimensional simulations, the magnetograms are required to be in complete flux balance, so we also correct them for imbalance using same technique as Mackay et al (2011). Data set 1 is already roughly in flux balance; the mean imbalance is 2.3% and the imbalance per pixel is at most 3 G, so is comparable to the noise level.…”
Section: Sdo/hmi Datamentioning
confidence: 99%
“…This is problematic for studies of magnetic topology because standard techniques (such as potential fields) applied to a sequence of photospheric magnetograms will not give the correct field line topology commensurate with an ideal evolution from one time to the next. To avoid this problem, A&A 539, A1 (2012) a number of studies have used time-dependent 3D simulations to model how topological structure develops in response to simple boundary motions (Milano et al 1999;Galsgaard et al 2003;Aulanier et al 2005;Masson et al 2009) or to boundary motions derived directly from observed magnetograms (Mackay et al 2011). But such time-dependent simulations inevitably suffer from numerical dissipation, leading to inaccuracies in magnetic topology.…”
Section: Introductionmentioning
confidence: 99%